Recycling of Precast Concrete Waste Sludge With Paper Mill and Biomass Ashes for Lightweight Granulated Aggregate Production - Moukannaa, Samira; Kursula, Kalle; Perumal, Priyadharshini; Ohenoja, Katja; Illikainen, Mirja (Frontiers in Materials, 2022)
The construction and demolition waste generation is increasingly evolving with the rapid urbanization, with more than a quarter of the produced waste being landfilled without further treatment or recycling strategy. Hence, sustainable management and valorization methods such as recycling in construction materials is becoming increasingly essential to tackle the economic and environmental burdens of landfilling waste. Construction and demolition waste recycling has been intensively studied. However, the present study proposes a promising solution for recycling construction and demolition wastes (CDWs) from the precast concrete waste sludge and ashes from paper mill sludge and biomass. Artificial lightweight aggregates were designed and produced by alkali activating a mixture of 50–90 wt% of dried and milled CDW with 3–25 wt% of ash and 5–35 wt% of blast furnace slag. The properties of the produced aggregates were assessed via density, water absorption, porosity, and crushing tests, in addition to microstructural characterizations using XRD and scanning electron microscopy SEM analysis. The optimum NaOH concentration was 8M with the highest mechanical properties and lowest efflorescence. The produced aggregates revealed a high crushing force of 82 N at 28 days with 50 wt% CDW, 15 wt% biomass ash, and 25 wt% blast furnace slag presenting a possible recycling pathway for such side-stream materials.